2010
DOI: 10.17221/2991-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory polyp in the middle ear of a dog: a case report

Abstract: Nasopharyngeal polyps are non-neoplastic masses, originating from the mucosa of the nasopharynx, the tympanic bulla or the Eustachian tube. Inflammatory polyps extending into the tympanic bulla cavity are a common cause of otitis media in cats. In dogs, however, occurrence of middle ear polyps has rarely been reported. The present report describes the findings of the clinical examination, diagnostic imaging and histopathological appraisal of a ten year old male dog with an inflammatory middle ear polyp arising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…7,8 A small number of published reports have described "otoliths" as "multiple, stonelike bodies imbedded in inflammatory soft tissue within the bullae" 8 or as "well-defined, smooth, round, singular, or multiple mineral concretions within the tympanic bullae" with a CT radiodensity of 500-1200 Hounsfield Units and a size ranging from approximately 1 × 2 to 10 × 10 mm. 7 Because histopathological analyses of "otoliths" have not been performed in any of the described cases of "otolithiasis," 7,8 it remains unclear whether the described "otoliths" are mineral concretions that indicate the occurrence of dystrophic mineralization associated with otitis media of different etiologies, 6,9,11 osseous tissue (i.e., HTBS), or rare middle ear osteomas 12 or exostoses 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 A small number of published reports have described "otoliths" as "multiple, stonelike bodies imbedded in inflammatory soft tissue within the bullae" 8 or as "well-defined, smooth, round, singular, or multiple mineral concretions within the tympanic bullae" with a CT radiodensity of 500-1200 Hounsfield Units and a size ranging from approximately 1 × 2 to 10 × 10 mm. 7 Because histopathological analyses of "otoliths" have not been performed in any of the described cases of "otolithiasis," 7,8 it remains unclear whether the described "otoliths" are mineral concretions that indicate the occurrence of dystrophic mineralization associated with otitis media of different etiologies, 6,9,11 osseous tissue (i.e., HTBS), or rare middle ear osteomas 12 or exostoses 13 .…”
Section: Discussionmentioning
confidence: 99%
“…2 Radiography, computed tomography (CT), and magnetic resonance imaging (MRI) represent valuable instruments to diagnose common middle ear diseases such as otitis media, (inflammatory) polyps, cholesteatomas, and neoplasms. [3][4][5][6] Diagnostic imaging findings commonly associated with middle ear disease include changes in the contour of the tympanic bulla, bone proliferation and/or osteolysis, or the presence of abnormal material in the middle ear cavity. 3,4 Occasionally, imaging findings of questionable clinical significance, formerly known as "otolithiasis," are observed on radiographs or CT scans of the tympanic cavities of dogs with variable signs of otitis media.…”
Section: Introductionmentioning
confidence: 99%
“…In gross appearance, nasopharyngeal polyps present as oval, white-to-pink, pedunculated masses with stalks originating from the mucosal lining of the nasopharynx, the eustachian tube, or the tympanic bulla [11]. To differentiate nasopharyngeal polyps from neoplastic lesions or other causes of infectious otitis, histopathologic examination of polyps should be performed [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, they are uncommon in dogs (Blutke et al, 2010;Greci & Mortellaro, 2016;Pratschke et al, 2003). There are only two detailed descriptive reports on aural polyp in dogs (Blutke et al, 2010;Pratschke et al, 2003). Blutke et al (2010) reported the case of a dog with a typical aural polyp, as seen in humans and cats.…”
Section: Introductionmentioning
confidence: 99%
“…There are only two detailed descriptive reports on aural polyp in dogs (Blutke et al, 2010;Pratschke et al, 2003). Blutke et al (2010) reported the case of a dog with a typical aural polyp, as seen in humans and cats. A polyp filled the middle ear without extending into the external auditory canal.…”
Section: Introductionmentioning
confidence: 99%